Caracterização anatomo-histopatológica e diagnóstica por PCR de Trypanosoma vivax em ovários de caprinos experimentalmente infectados - Rodrigues, Carla Monadeli Filgueira (Universidade Federal Rural do Semi-Árido, 2014)
This study aimed to determine the rate of ovarian follicles degeneration and search for the presence of parasite DNA by PCR in ovarian tissue from goats experimentally infected with Trypanosoma vivax. Six goats, females, adults were infected with 1.25 x105 trypomastigotes of T. vivax and four others formed the control group. After 60 days of infection, was collected from the ovaries and performed the pathological examination. Samples of ovaries were taken to perform the polymerase chain reaction (PCR). The parasitemia was observed from the third day post-infection (dpi) with peaks in the 7-14th dpi. Histological analysis showed that the group of infected goats, the average value of follicles was significantly lower (P <0.05) compared to the control group. As the stage of development in the control group, the number of primordial and primary follicles was significantly higher (p <0.05) than the secondary and tertiary. As for integrity, no significant difference in the average value of the follicles degenerate type I between control and infected. The number of follicles degenerate type II was significantly higher (p <0.05) in the infected group than in the control group, and most degenerate type II follicles were primordial and primary. The analysis of T. vivax in ovarian tissues by PCR specific for T. vivax (TviCatL-PCR) showed amplification of a DNA fragment of approximately 177 bp was observed in right and left ovaries of all the goats of the infected group. The result of PCR, however, was negative for all samples in the control group. The follicular degeneration associated with the presence of the parasite in the ovaries, as detected by PCR, suggesting the involvement of the parasite in the etiopathogenic mechanism of reproductive harm
Anatomic and histopathologic description and diagnosis by PCR of Trypanosoma vivax in ovaries of goats experimentally infected
Keywords: Goats, Trypanosoma vivax, follicular degeneration and PCR; Caprino; Trypanosoma vivax; Degeneração folicular; PCR; CIENCIAS AGRARIAS::MEDICINA VETERINARIA